Media visual untuk meningkatkan keterampilan membaca siswa dalam mendukung pendidikan berkualitas SDGs - Bunga Putri Maulia; Lee Yii Tyng; Abdullah Kafabih (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
Reading proficiency is crucial for academic success, yet many university students, including those at Universitas Negeri Yogyakarta, struggle with comprehension due to limited vocabulary, lack of critical thinking, low motivation, and traditional teaching methods; thus, innovative strategies like visual media are needed to foster interest and improve reading skills. One such medium, the wall magazine, has shown promise in primary education but remains underexplored in higher education, prompting this study to evaluate its effectiveness in enhancing students’ reading abilities and to provide insights for more engaging and interactive pedagogical approaches. This study employed a descriptive qualitative method with purposive sampling, involving 39 second-semester English Education students at Yogyakarta State University and several key informants to explore the effectiveness of wall magazine media in enhancing reading skills. Data were collected through observation, interviews, and documentation, then analyzed using qualitative descriptive techniques with triangulation strategies to ensure validity and credibility. This study confirms that wall magazine media effectively enhances reading skills by increasing student motivation, comprehension, and engagement. The project-based and collaborative nature of the media fosters critical thinking, creativity, and a sense of ownership in learning. While students and lecturers responded positively, improvements in content updates and display logistics are still needed. Therefore, integrating wall magazine projects into the curriculum offers a sustainable, student-centered approach to developing literacy and 21st-century skills.